Debt Settlement Strategy: Concurrent Creditor Rights And Debtor Asset Security - Agung Wijayanto; Sunny Ummul Firdaus; Heri Hartanto (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
This research analyzes debt settlement strategies in fulfilling the rights of concurrent creditors to the debtor's assets used as debt collateral, considering Aristotle's concept of proportional justice. Through a normative juridical approach, this research explores applicable laws and regulations, case studies, and related literature to understand the dispute resolution mechanism between concurrent creditors and preferred creditors. The results show that the main challenge in achieving proportional justice for concurrent creditors arises when the debtor's assets are insufficient to fulfill all debt obligations. Some debt settlement strategies identified include debt restructuring, rescheduling payments, and mediation or arbitration mechanisms. Discussion of the research results highlighted the importance of legal protection for concurrent creditors in debt settlement, which aligns with Aristotle's concept of proportional justice. Policy recommendations include the expansion of the court's authority to handle cases involving conflicting creditor rights. This research is expected to contribute to the development of fairer and more effective policies for concurrent creditors and provide practical guidance for legal practitioners in handling cases involving debtor asset collateral.